Improvement of the model of power losses in the pulsed current traction motor in an electric locomotive - Goolak, S. O.; Sapronova, S. Yu.; Tkachenko, V. P.; Riabov, Ie. S.; Batrak, Ye. O. (ПП "Технологічний Центр", 2020)
When studying transients in pulsed current traction motors, it is important to take into consideration the eddy and hysteresis losses in engine steel. Magnetic losses are a function of the magnetization reversal frequency, which, in turn, is a function of the engine shaft rotation frequency. In other words, magnetic losses are a function of time. Existing calculation procedures do not make it possible to derive the instantaneous values of magnetic losses as they are based on determining average losses over a period. This paper proposes an improved model of magnetic losses in the steel of a pulsed current traction motor as a function of time, based on the equations of specific losses. The adequacy criteria of the procedure for determining magnetic losses in electrical steel have been substantiated: the possibility to derive instantaneous values of magnetic losses in the magnetic material as a function of time; the possibility of its application for any magnetic material; and the simplicity of implementation. The procedure for determining magnetic losses in the steel of a pulsed current traction motor has been adapted by taking into consideration the magnetic properties of steel and the geometry of the engine’s magnetic circuit. In order to determine the coercive force, the coefficient of accounting for the losses due to eddy currents, as well as the coefficient that considers the losses on hysteresis, the specifications’ characteristics of specific losses in steel have been approximated using the pulsed current traction motor as an example. The simulated model of magnetic losses by the pulsed current traction motor has demonstrated the procedure for determining average magnetic losses and time diagrams of magnetic losses. The proposed model for determining magnetic losses could be used for any magnetic material and any engine geometry under the condition of known material properties and the characteristics of change in the magnetic flux density in geometry.

При дослідженні перехідних процесів в тягових двигунах пульсуючого струму важливим є врахування вихрових та гістерезисних втрат в сталі двигуна. Магнітні втрати є функцією частоти перемагнічування, яка, в свою чергу, є функцією частоти обертання валу двигуна. Іншими словами – магнітні втрати є функцією часу. Існуючі методики розрахунку не дозволяють отримати миттєві значення магнітних втрат, а основані на визначенні середніх втрат за період.Запропоновано удосконалену модель магнітних втрат в сталі тягового двигуна пульсуючого струму, як функції часу, на основі рівнянь питомих втрат.Обґрунтовано критерії адекватності методики визначення магнітних втрат в електротехнічній сталі: можливість отримання миттєвих значень магнітних втрат в магнітному матеріалі, як функції часу; можливість застосування для будь-якого магнітного матеріалу; простота реалізації. Адаптовано методику для визначення магнітних втрат в сталі тягового двигуна пульсуючого струму шляхом врахування магнітних властивостей сталі та геометрії магнітного ланцюга двигуна. З метою визначення коерцитивної сили, коефіцієнту врахування втрат на вихрові струми та коефіцієнту врахування втрат на гістерезис апроксимовано паспортні характеристики питомих втрат в сталі на прикладі тягового двигуна пульсуючого струму. На імітаційній моделі магнітних втрат тягового двигуна пульсуючого струму продемонстровано методику визначення середніх магнітних втрат та часових діаграм магнітних втрат. Запропонована модель визначення магнітних втрат може застосовуватись для будь-якого магнітного матеріалу і будь-якої геометрії двигуна при умові відомих властивостей матеріалу і характеристик зміни щільності магнітного потоку в геометрії.
Удосконалення моделі втрат потужності тягового двигуна пульсуючого струму електровоза
Keywords: magnetic losses; eddy currents; hysteresis; traction motor; universal magnetic characteristic; магнітні втрати; вихрові струми; гістерезис; тяговий двигун; універсальна магнітна характеристика